The Native Homeland of The Indo-Europeans: A Historical Study (Raparin Journal of Humanities (RJH), 2025)
The homeland of the Indo-Europeans remains one of the most significant and debated topics in historical and linguistic studies, sparking widespread controversy among historians, archeologists, and linguistics due to the variety of evidence and its limitations. Identified primarily through linguistic studies, the Indo-Europeans have been referred to by various names, and their origins, migrations and eventual spread across ancient civilizations have greatly influenced the political and cultural developments of these regions. They played a pivotal role in shaping the ancient world, establishing influential kingdoms and empires, particularly in the ancient Near East, where their presence spanned from the second millennium BCE to the end of the first millennium BCE. The question of their original homeland has long been a subject of scholarly debate, dividing researchers into various schools of thought. Consequently, multiple regions in Asia and Europe, including India, Central Asia, Anatolia, the Caucasus, Northern Europe, Central Europe, Southeastern Europe, and Southern Russia, have been proposed as their homeland. However, a definitive and universally accepted homeland for the Indo-Europeans has yet to be determined. This study, titled ‘The Homeland of Indo-Europeans: a Historical Study’, is divided into two main parts: (1) the term and appearance of Indo-Europeans in History, and (2) The homeland of the Indo-Europeans.